Improved Learning Outcomes Of Social Sciences Lessons Through Google Meet Assisted Powerpoint Media - Utami, Tri (Universitas Sebelas Maret, 2020)
This research is a classroom action research (CAR) which aims to improve student learning outcomes in social studies subject matter through the use of the Google Meet application with the help of PowerPoint learning media. The sample in this study amounted to 12 students. The research method used is Classroom Action Research (CAR) in two cycles consisting of two meetings in each cycle. The stages of each cycle are planning, implementation, observation and reflection. In the first cycle, the students who completed the post test were 66.67%, and in the second cycle 91.67%. From this analysis, it can be seen from the increase in student learning outcomes in cycle I to cycle II. It can be concluded that the use of the google meet application with the help of powerpoint learning media can improve student learning outcomes, especially in Social Studies class VI SDN Randugunting 7 Tegal City.